Формулы тригонометрии

Tg(α+β)=(tgα+tgβ)/(1-tgα-tgβ); tg(α-β)=(tgα-tgβ)/(1+tgα-tgβ)

Ctg(α+β)=(ctgα-ctgβ-1)/(ctgβ+ctgα); ctg(α+β)=(ctgα-ctgβ+1)/(ctgβ-ctgα)

Sinα+sinβ=2sin½(α+β)cos½(α-β); sinα-sinβ=2cos½(α+β)sin ½(α-β)

Cosα+cosβ=2cos½(α+β)cos½(α-β); cosα-cosβ=-2sin½(α+β)sin ½(α-β)

A-sinx+b-cosx=Ö(a²+b²)sin(x+β), где tgβ=b/a

Tgα± tgβ=sin(α+β)/(cosα-cosβ); ctgα± ctgβ=sin(β±α)/(sinα-sinβ)

Sin²α-sin²β=cos²β-cos²α=sin(α+β)sin(α-β)

Cos²α-sin²β=cos²β-sin²α=cos(α+β)cos(α-β)

Sinα-sinβ=½[cos(α-β)-cos(α+β)]; cosα-cosβ=½[cos(α-β)+cos(α+β)]

Sinα-cosβ=½[sin(α+β)+sin(α-β)]

Tgα-tgβ=(tgα+tgβ)/(ctgα+ctgβ)=-(tgα-tgβ)/(ctgα-ctgβ)

Ctgα-tgβ=(ctgα+tgβ)/(tgα+ctgβ)=-(ctgα-tgβ)/(tgα-ctgβ)

Ctgα-ctgβ=(ctgα+ctgβ)/(tgα+tgβ)=-(ctgα-ctgβ)/(tgα-tgβ)

Sin½α=±Ö((1-cosα)/2); sinα=(2tg½α)/(1+tg² ½α)

Sin2α=2 sinα-cosα; sin3α=3sinα-4sin³α

Sin²α=½(1-cos2α); sin³α=(3 sinα – sin 3α) / 4

Cos½α=±Ö[(1+cosα)/2]; cosα=(1-tg² ½α)/(1+tg² ½α)

Cos2α=cos²α-sin²α=1-2 sin²α=2cos²α-1; cos3α=4cos³α-3 cosα

Cos²α=½(1+cos2α);cos³α=(3cosα+cos3α)/4

Tg½α=sinα/(1+cosα)=(1-cosα)/sinα= ±Ö((1-cosα)/(1+cosα))

Tgα=(2tg½α)/(1-tg² ½α); tg2α=(2tgα)/(1-tg²α)=2/(ctgα-tgα)

Tg3α=(3tgα-tg³α)/(1-3tg²α)=tgα-tg(π/3+α)-tg(π/3-α)

Ctg½α=sinα/(1-cosα)=(1+cosα)/sinα=±Ö((1+cosα)/(1-cosα))

Ctgα=(ctg² ½α-1)/2ctg ½α; ctg2α=(ctg²α-1)/2ctgα=½(ctgα-tgα)

Ctg3α=(3ctgα-ctg³α)/(1-3 ctg²α)

Tg(¼п+α)=(sinα+cosα)/(sinα-cosα); tg(¼п-α)=(sinα-cosα)/(sinα+cosα)


Формулы тригонометрии